El error de hecho como vicio invalidante de los Actos Administrativos de desvinculación de los trabajadores con nombramiento definitivo en FLOPEC ep. - TORRES AYALA, PATRICIO LEANDRO (2022)
In this research, the consequences of the error of fact as an invalidating vice of the administrative act are determined, based on the case related to the dismissal memorandum sent to the workers of the Public Company Flota Petrolera Ecuatoriana, in the month of May 2020; through an analysis in which it is established that the memorandum, is an administrative act, and the formation of its constituent element, such as the will, which was affected by an erroneous perception, originates a discordance between the real facts and the purpose of the administrative act, and influences its motivation, which led to conclude that an administrative act vitiated by a mistake of fact has as psychological factors produced in the person who issues the act and breaks constituent elements, essential and valid elements of the administrative act, configuring serious and substantial components, which impair its existence, validity and execution within the legal world, damaging subjective rights for the administered, defects that cannot be corrected, causing its absolute and full nullity in accordance with the constitutional and legal norm.